Effective Strategies for Boosting Critical Thinking and Learning Motivation: The PQ4R Approach - Lutfianasari, Ulfa; Nasikah, Ilmi (Journal of Educational Chemistry (JEC), 2024)
This research aims to determine the effectiveness of the PQ4R learning strategy on students' critical thinking skills and learning motivation. This research uses quasi-experimental research with a nonequivalent control group design. The population in this study was part of class XI MIPA at MA Negeri Kendal. Sampling was carried out using the cluster random sampling technique. The sample used in this research was 36 students of class XI MIPA 4 as the experimental class and 32 students of class XI MIPA 3 as the control class. The research results showed that the critical thinking skills t-test obtained a significance value (Sig.) 0.000 < 0.05, meaning there were differences in critical thinking skills between the experimental and control classes. Based on the results of the N-Gain test, critical thinking skills for the experimental class were 0.4418, and for the control class were 0.1483. The results of the t-test research on learning motivation obtained a significance value (Sig.) 0.001 < 0.05, meaning there is a difference in learning motivation for the experimental and control classes. Based on the results of the N-Gain test, the learning motivation for the experimental class was 0.3315, and the control class was 0.1529.  This research concludes that the effect of the effectiveness of using the PQ4R learning strategy on critical thinking skills and learning motivation in the experimental class is higher than in the control class.